Estudo do comportamento fisiológico de cepas de leveduras frente às condições do meio de cultivo visando processos de fermentação alcoólica - Martins, Gisele Marta [UNESP] (2015)
The microorganisms can show different behavior in different conditions of cultivation. In biotechnological processes, this knowledge allows that fermentation parameters to be controlled in order to optimize costs and yield. In this work it was standardized a test of ethanol production by yeast from xylose using Petri dishes assay, which allowed the recognition of 17 xylose fermenting yeasts. Using submerged fermentation it was detected that Candida shehatae, var. shehatae PT1-1BASP produced 12 g L -1 of ethanol and Aureobasidium pullulans LB3.1, 7 g L-1. Ethanol production by these two strains was evaluated with respect to fermentation parameters, such as tolerance to compounds recognized as inhibitors of growth of yeast, temperature of incubation, initial pH of the must, concentration of the inoculum and nutrient addition. The definition of the best fermentation conditions increased the xylose consumption by both strains, while it decreases the production of biomass and increased ethanol yield by A. pullulans LB3.1. The C. shehatae PT1-1BASP and A. pullulans LB3.1 reached a maximum ethanol yield of 18.7 gL-1 and 17.5 gL-1, respectively. Besides these two yeasts, Brettanomyces bruxellensis the ISA 2211, a wine contaminating strain, was evaluated with respect to SO2 tolerance in the face of variations in culture conditions. The addition of vitamins and yeast extract to must increased the yeast resistance to sulfur dioxide, while the presence of ethanol, in combination with SO2, had greater growth inhibition. It was also studied in this work, the ability of B. bruxellensis ISA 2211 to use the ρ-coumaric acid as a carbon source, noting that the growth of yeast in that condition was dependent on the acid concentration in the medium, not tolerating concentrations high than 5 mmol. L-1